An Essencist Evaluation of Socio-Economic Impacts of Coronavirus Disease (COVID-19) Pandemic in Nigeria - Ekanem, Samuel Asuquo; Imarenezor, Edobor Peter Kenneth; Okolisah, Chinenye Precious (Richtmann Publishing, 2020)
There is a tripartite global crises of social, economic and health unlike any in the past almost eight decades history of the United Nations that is fast killing people, increasing and spreading human woes and sufferings with an unending existential calamities. This is indeed, beyond health, economic and social crises. It is evidently human existential crises that have the potency and potential to bring about existential eclipse of the human race. The coronavirus disease (COVID-19) is wreaking havoc on societies at their core. With the International Monetary Fund (IMF) reassessment of the prospect for growth for 2020 and 2021, and the declaration that there is a global recession that is as bad as or even worse than the 2009 situation, Nigeria socio-economic survival is at risk. The only hope of any recovery in 2021 is if the country succeeds in containing the pandemic and take sound and necessary economic decisions and measures. The only roadmap for the socio-economic survival of the country will depend on the proactive management approaches, health policy framework and leadership that will comprehensively address the several social conditions that have to do with health education and literacy level, both nationally and internationally in the areas of economic stimulus that will demand both government and citizens partnerships and the constitution of National Technical Committee on Coronavirus (NTCC) that will relate with a global technical body. The efficient execution of these policy and ideas will certainly demand the total cooperation of all strata of the society, which will include governmental agencies, information experts, civil societies, health experts, educationists and the citizens. What the paper therefore advocates is a multi-disciplinary and interdisciplinary approaches anchored on a sound philosophy through the educational process towards overcoming this 21st century invisible monster. Our approach in this paper will be a combination of analysis and philosophical evidential speculation, which will inspire creativity that will match the novel nature of the crisis.